2015
DOI: 10.4018/ijmmme.2015100101
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength Improvement of Welded Joints Prepared by Vibratory Welding Process

Abstract: Vibration techniques have been used in welding for improving the mechanical properties of metals in the last few decades. In the present work, vibratory setup has been used for inducing mechanical vibrations into the weld pool during welding. The designed vibratory setup produces the required frequency with the amplitude and acceleration in terms of voltages. An increase in the flexural strength of the weld pieces in to the heat affected zone (HAZ) has been observed. The increase in mechanical properties is at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Authors observed that providing vibrations during welding process enhances the mechanical properties. Refined grain structure was the main reason for the improvement of mechanical characteristics (Rao et al, 2015a(Rao et al, , 2015b(Rao et al, , 2015c. Kalpna et al explored the vibration amplitude effect on mild steel and stainless steel weld connections (Kalpana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Authors observed that providing vibrations during welding process enhances the mechanical properties. Refined grain structure was the main reason for the improvement of mechanical characteristics (Rao et al, 2015a(Rao et al, , 2015b(Rao et al, , 2015c. Kalpna et al explored the vibration amplitude effect on mild steel and stainless steel weld connections (Kalpana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By varying the input parameters of the metal engravers like voltage, frequency and vibrational period the process is done and enhancement of properties are taken place. P.Govinda Rao., et.al., [7][8][9][10][11][12] introduced the new experimental setup for inducing mechanical vibrations through unbalanced weight's. By considering the input parameters like vibrating period for specimens and voltage of the vibromotor.…”
Section: Introductionmentioning
confidence: 99%
“…Authors observed that post weld vibratory treatment will not influence the crystal structure, the increase in all properties are related to the crystal structure only. Finally, General regression neural network technique (GRNN) based tool has been developed for estimating tensile strength, impact strength, flexural strength and hardness for given input parameters [22][23][24][25][26][27][28][29]. Overcome the disadvantages of the stated above, a vibratory set up have been developed in the current investigation to enrich the mechanical properties of welded joints with the following objectives:…”
Section: Vibratory Weldingmentioning
confidence: 99%